2021
DOI: 10.21608/jrciet.2021.198531
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Presentation Patterns of the Infographic (Static / Animated) and learning Styles (global/ sequential) in Adaptive Learning Environment and its Effect on the Development of Programming Skills of Secondary students

Abstract: his research aimed at figuring out the effect of interaction between Presentation Patterns of the Infographic (static/ animated) and the learning styles (global/sequential) in an adaptive learning environment and its Effect on the Development of Programming Skills of Secondary school students, To such a purpose, a PHP-based programming skills list and an adaptive learning environment-related criteria have been prepared. Instruments of the study consisted of an achievement test and an observation sheet.The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study by Sabry et al (2021) investigated the effect of interaction between presentation patterns of the infographic (static/animated) and the learning styles (global/sequential) in an adaptive learning environment on the development of programming skills of secondary school students. The results showed a positive effect of such interaction between the patterns of the infographic and the learning styles in an https://doi.org/10.17509/jik.v21i1.62255…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Sabry et al (2021) investigated the effect of interaction between presentation patterns of the infographic (static/animated) and the learning styles (global/sequential) in an adaptive learning environment on the development of programming skills of secondary school students. The results showed a positive effect of such interaction between the patterns of the infographic and the learning styles in an https://doi.org/10.17509/jik.v21i1.62255…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies revealed that adaptive learning systems promise to improve students' skills, engagement, and overall educational experience. Toktarova (2022) and Sabry et al (2021) demonstrate the effectiveness of adaptive systems in enhancing specific skills, while Clark et al (2022) highlight their positive impact on classroom environment and motivation. El-Sabagh (2021) underscores their potential to increase student engagement, although their influence on learning outcomes may be limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kankaew and Suksudthi (2021) defined infographics as a collection of imagery, charts, and minimal text that gives an easy-to-understand overview of a topic. Sabry (2021) describes info-graphic as a visual representation of any kind of information or data it can be in form of static and animated images which are used for educational, marketing and scientific purposes. From the following author's input on the concept of the infographic, it is safe to say that info-graphics is a visual graphical design that is used to interpret data and information into simple bits for easier cognition by learners or available audiences.…”
mentioning
confidence: 99%